CAN CONTEMPORARY AFRICA RESPOND TO ECOLOGICAL BAGGAGE FROM GLOBALIZATION WITH GLOBAL BEST PRACTICE? - Azuwike, Okechi Dominic; Eboh, Emmanuel A (African Journal of Social and Behavioural Sciences, 2020)
The present effort identifies encumbrances to Africa's participation in global best practices and appraises Africa's chances of scaling up to these ideals. It identifies topical issues in the literature through in-depth literature review while identifying new theoretical issues of importance in the globalization of ecological challenges to Africa and concurrent failure to extend the right ecological and ethical standards to Africa. What is at issue is Africa's response and therefore Africa's will, abilities, persuasions, and philosophical leaning that impinge on her exercise of agency. A number of factors have been identified which hamper quality of Africa's response to globalization's ecological onslaught. These include weakness of the institutional framework and related near absence of the right policy framework. For instance, receiving shipments of radioactive waste in 1986 was Nigeria's rude awakening to her lack of not just waste policy but general environmental management framework. There is a debilitating humanistic bent in societies pandering to a poverty narrative; a poor administrative culture of regulatory agencies; massive internal displacement overhang compromising preparedness; a socio-political environment of impact assessment that compromises sound business case development for projects from subjective government waivers to uninformed stakeholders; weakness of civil societies; fixation with raw material export economy; defective political structures that concentrate powers emasculating local initiatives; colonial hangover of educational elitism and offer of 'standards holiday' and 'standards havens' to bait foreign investments. Other problems include ambitious interventionist projects; neglect of extant product lifecycle management provisions, global inequality and a failure to mobilize a cultural bulwark against undue foreign designs. The study reviews possibilities open to Africa given her current place in the world as a major user and re-user of used items. It therefore mooted the idea of Africa championing a product last user/re-user principle that will allow the continent benefit from comprehensive product lifecycle management arrangements as provider of final resting place for products that have been used in other lands. The study concludes by reviewing prospect of appropriate response from Africa and sets agenda for the African continent on the subject of integrating best practices into ecological management. A more proactive engagement of the subject of globalized ecological challenge than reactionary steps to which the continent has grown familiar is suggested.